Raman spectroscopy-based water content is a negative predictor of articular human cartilage mechanical function. Issue 2 (February 2019) - Unal, M.; Akkus, O.; Sun, J.; Cai, L.; Erol, U.L.; Sabri, L.; Neu, C.P.
Summary: Objective: Probing the change in water content is an emerging approach to assess early diagnosis of osteoarthritis (OA). We herein developed a new method to assess hydration status of cartilage nondestructively using Raman spectroscopy (RS), and showed association of Raman-based water and organic content measurement with mechanical properties of cartilage. We further compared Raman-based water measurement to gravimetric and magnetic resonance imaging (MRI)-based water measurement. Design: Eighteen cadaveric human articular cartilage plugs from 6 donors were evenly divided into two age groups: young ( n = 9, mean age: 29.3 ± 6.6) and old ( n = 9, mean age: 64.0 ± 1.5). Water content in cartilage was measured using RS, gravimetric, and MRI-based techniques. Using confined compression creep test, permeability and aggregate modulus were calculated. Regression analyses were performed among RS parameters, MRI parameter, permeability, aggregate modulus and gravimetrically measured water content. Results: Regardless of the method used to calculate water content (gravimetric, RS and MRI), older cartilage group consistently had higher water content compared to younger group. There was a stronger association between gravimetric and RS-based water measurement ( R g 2 = 0.912) than between gravimetric and MRI-based water measurement ( R c 2 = 0.530). Gravimetric and RS-based water contents were significantly correlated with permeability and aggregate modulus whereas MRI-based water measurement was not. Conclusion: RS allows for quantification of different water compartments in cartilage nondestructively, and estimation of up to 82% of the variation observed in the permeability and aggregate modulus of articular cartilage. RS has the potential to be used clinically to monitor cartilage quality noninvasively or minimally invasively with Raman probe during arthroscopy procedures.